Angka Lempeng Total (ALT), Coliform, Escherichia coli dan Staphylococcus aureus pada urutan babi di wilayah Kecamatan Banjarangkan, Bali - Dewi, Komang Nikastri Tussning; Darmayasa, Ida Bagus Gede; Sudatri, Ni Wayan (Jurnal Biologi Udayana; Vol 28 No 1 (2024): JURNAL BIOLOGI UDAYANADO - 10.24843/JBIOUNUD.2024.v28.i01.p12, 2024)
Urutan or Balinese sausage is a traditional food product that is widely demanded and sold in the province of Bali. Improper processing, handling and storage will result in microbial contamination that causes food poisoning including Coliform , Escherichia coli , and Staphylococcus aureus . The purpose of this study was to determine the total bacterial contamination of Total Plate Count (TPC), Coliform , Escherichia coli , and Staphylococcus aureus in urutan babi sold in Banjarangkan District, Bali. Sampling was obtained from recording urutan babi order traders in Banjarangkan Subdistrict using purposive sampling method. The parameters tested were ALT and Staphylococcus aureus by pour plate method, Coliform by Most Probable Number (MPN) method and Escherichia coli by streak plate method. Total Plate Count (TPC) and Staphylococcus aureus content fluctuated between 10 2 – 10 5 CFU/g within 3 weeks of testing, 7 out of 15 samples were positive for Coliform , 15 samples were contaminated with Escherichia coli below <3 × 10 2 MPN/100g. A total of 12 out of 15 samples (80%) were not suitable for consumption for the TPC test, 8 out of 15 samples (53.3%) were suitable for consumption for the Coliform test, 12 out of 15 samples (80%) were suitable for consumption for the S. aureus test, and all samples were suitable for consumption for the E. coli test according to the quality standards set by BPOM No. 13 of 2019 and SNI 7388: 2009.